Implementation of Interprofessional Collaboration in Type 2 Diabetes Mellitus Care in Health Service Facilities - Rahmat Bakhtiar; Krispinus Duma; Muhammad Aminudin (Husada Mahakam, 2020)
Management of Type 2 Diabetes Mellitus (T2DM) treatment in Indonesia had not been optimal, marked by the increasing incidence of both macro and micro complications which have an impact on high morbidity and mortality rates. As a chronic disease, the priority of T2DM management strategies was early detection and prevention of complications that could be done with a collaborative multi-disciplinary team approach. This study aimed to analyze the application of inter-professional collaboration in T2DM services in health care facilities in East Kalimantan. This research method was cross-sectional. A total of 120 T2DM patients who had received treatment both at the hospital and at the Primary Health Centre were involved in this study. The research variables were interpersonal collaboration, communication, team decision making, and conflict management. The results of the observations showed that the interaction of officers in the T2DM service activities went well and gave each other information among the team about conditions and management plans. Team communication played a role in the implementation of inter-professional collaboration on the treatment of T2DM in both hospitals and health centers. We believe that effective communication will reduce various barriers such as professional egos, skill gaps, or team knowledge which will increase the team's motivation to provide quality service.